1988
DOI: 10.1093/jnci/80.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mdr (P-glycoprotein) Gene in Chinese Hamster Digestive Tracts1

Abstract: P-glycoprotein has been shown to be responsible for multidrug resistance in mammalian cells. However, its physiological roles in normal cells are not known. The gene encoding this protein has been shown to express at a relatively high level in human digestive tracts. In the present study, in situ hybridizations were employed to determine the expression of this gene in gastrointestinal tissues. Epithelial cells in the villi of small intestine, colon, and stomach were rich in the P-glycoprotein gene transcript. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…MDR gene expression in the intestinal epithelium has been reported by numerous investigators in human (Fojo et al, 1987;Thiebaut et al, 1987), mouse (Croop et al, 1989;Buschman et al, 1992), hamster (Mukhopadhyay et al, 1988;Bradley et al, 1990) and rat (Trezise and Buchwald, 1991). These studies have all identified the class I gene (MDR1, mdr1a and pgp1 respectively) as the only isoform in the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 90%
“…MDR gene expression in the intestinal epithelium has been reported by numerous investigators in human (Fojo et al, 1987;Thiebaut et al, 1987), mouse (Croop et al, 1989;Buschman et al, 1992), hamster (Mukhopadhyay et al, 1988;Bradley et al, 1990) and rat (Trezise and Buchwald, 1991). These studies have all identified the class I gene (MDR1, mdr1a and pgp1 respectively) as the only isoform in the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 90%
“…MDR1-type P-glycoprotein has been found in the apical membrane of the intestinal epithelial cells (Mukhopadhyay et al 1988), in the biliary canalicular membrane of hepatocytes, and in the lumenal membrane of proximal tubular epithelial cells in the kidney (Thiebaut et al 1987(Thiebaut et al , 1989. High levels of MDR1 P-glycoprotein have been found in the lumenal membrane of the endothelial cells that line small blood capillaries and form the blood-brain and blood-testis barrier (Thiebaut et al 1989;Cordon-Cardo et al 1989Tsuji et al 1992).…”
Section: Mice With a Genetic Disruption (Knockout) Of The Multiple Drmentioning
confidence: 99%
“…Consistent with this idea, it has been suggested that P-glycoproteins play an important role in the excretory systems of normal animals. In situ hybridization (36) and immunocytochemical analyses (18,46) have demonstrated high levels of mdr transcripts or P-glycoprotein on the lumenal surface of several epithelial cell types, including hepatocytes, intestinal mucosal epithelial cells, and kidney proximal tubule cells.…”
mentioning
confidence: 99%